Selection Parameters for Production Traits in a Duroc Population - Razvan Alexandru Popa; Dana Popa; Carmen Nicolae; Livia Vidu; Monica Marin; Elena Pogurschi; Marius Maftei; Nicolae Isfan (Scientific Papers Animal Science and Biotechnologies, 2023)
The goal of this paper is to estimate the genetic parameters for production traits in a pattern pig line. The estimation of the variance-covariance components is a very important step in animal breeding because these components are necessary for: (1) estimation of the genetic parameters, (2) prediction of the breeding value and (3) the design of animal breeding programs. The estimation of the selection parameters (h2, rG, rF, rE) is the first step in the development of a Duroc line breeding program, using artificial insemination.